DAMPAK KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN (STUDI KASUS PADA PERUSAHAAN SUB SEKTOR KERTAS DI BURSA EFEK INDONESIA) - M. Rimawan; Puji Muniarty (Nusantara Hasana Journal, 2025)
his research aims to determine the influence of return on assets, debt to equity ratio, current ratio and company size on company value in companies in the paper sub sector. This type of research is associative analysis with a quantitative approach. The population of this research are all paper sub-sector companies listed on the Indonesia Stock Exchange from 2019 to 2023. The total sample is 6 companies listed on the IDX. The sampling technique used was purposive sampling. The data collection techniques used are documentation techniques and library techniques. In this research, the data analysis techniques used are classical assumptions, multiple linear regression tests, correlation and determination coefficients, hypothesis testing consisting of the t test and f test with the help of the SPSS version 26 program. The results show that the variables Return on Assets and Debt to equity have a significant effect on company value, while the current ratio variable has no effect on company value. Meanwhile, simultaneously it has a significant influence on company value.